Il fondo di plaques photographiques dell’Institut Français de Florence (1907-1919). Didattica e propaganda nel primo istituto culturale del mondo - Gallicchio, Alessandro (Rivista di studi di fotografia. Journal of Studies in Photography, 2015)
A series of photographic plates in the collection of the Institut Français of Florence (founded in 1907) sheds new light on the cultural exchange between France and Italy in the early years of the 20th century. From the outbreak of WWI, the institute promoted illustrated conferences encouraging Italian soldiers to go to war. This article discusses teaching with images and underscores how this approach was central for both art history and war propaganda.